The Status of Gillnet, Stow-net and Trawl Fishing in the Soc Trang-Bac Lieu Coastal Region, Vietnam - Hung, Ha Phuoc; Quynh , Vo Le Khanh; Hieu, Mai Van (Journal of Fisheries and Environment, 2022)
Gillnet, stow-net and trawl are the three main fishing gears used by coastal fishers in Soc Trang and Bac Lieu provinces in the lower Mekong Delta, but catches from all three have been declining in recent years. We investigated the species composition of fish stocks along this coastline of Vietnam, and examined the current status of fishers and the gears they use, their fish catches, and the economic returns from each of the three net types. We also assessed the awareness of climate change among fishers, and the actions they take to adapt to its consequences. Annual fish catches were low: 11.9 t·boat-1·year-1 for stow-netters, 9.3 t·boat-1·year-1 for trawlers, and 4.4 t·boat-1·year-1 for gillnetters. Despite its low catch rate, the gillnet fishery provided the highest annual profit (4,364 USD·boat-1·year-1) because it caught higher value fish due to both their species and size. The rate of return was 0.52 for the gillnet fishery, 0.52 for the stow-net fishery and 0.33 for the trawl fishery. Overall, fishers had a low educational status and poor understanding of climate change, and only about two-thirds of them had short-term solutions to deal with changing weather and sea conditions. Current fishing practices, coupled with climate change are likely to lead to further declines in fish stocks and catches and threaten the livelihoods of near-shore coastal fishers.